Single–spin asymmetries in electron–proton and photon-proton scattering in the Bethe–Heitler processes induced by loop corrections - Afanasev, A.V.; Konchatnij, M.I.; Merenkov, N.P. (Вопросы атомной науки и техники, 2007)
The single–spin target asymmetries in the hard electroproduction process e⁻ + p → e⁻ + γ + p and in the e⁺e⁻-pair photoproduction γ + p → e⁺ + e⁻ + p, induced by the loop radiative corrections to the vertex part of lepton interaction are considered. The physical reason to appearance such a kind of asymmetries is the nonzero imaginary part of the respective Bethe-Heitler amplitudes (on the level of radiative correction). The single–spin target asym-metries at unpolarized ingoing electron or photon beams and at arbitrary polarizations of the target proton for condi-tions of CLAS (Jefferson Lab, USA) and HERMES (DESY) experiments are calculated.